Translation of the absorbed dose in the mobile phone to organ doses of an ICRP voxel phantom using MCNPX simulation of an Ir-192 point source. (August 2021) - Discher, M.; Eakins, J.; Woda, C.; Tanner, R.
Abstract: Monte Carlo modelling has been performed to simulate aspects of the CATO exercise, which recreated the exposure of individuals on a bus to an Ir-192 point source. The modelling allowed a comparison and check of the measured data provided in (Rojas-Palma et al., 2020; Discher et al., 2021), and an investigation into the dose conversion coefficients that are required in order to use fortuitous dosemeters as indicators of absorbed doses to individuals; a conversion factor of 0.22 ± 0.01 was found to be appropriate to relate the phone dose to the average organ dose. The modelling also allowed some of the parameters of the experiment to be varied, and their impacts explored. In general, measured and modelled data agreed acceptably, with similar average doses and broadly similar variations in the results as a function of organ type. Highlights: MCNPX simulations of an ICRP 110 male voxel phantom combined with a model of a mobile phone. Comparison of simulated results to experimental results of organ absorbed doses from an Ir-192 point source exposure. Generation of conversion data from measured doses to average organ doses.